Analis Dampak Fintech terhadap Kinerja UMKM Sektor Food and Beverage di Jakarta Utara - Slamet Hariyanto; Komang Agung Wira Dharma; Cicely Delfina H (Journal of Management and Creative Business, 2026)
The development of financial technology (fintech) in Indonesia plays a significant role in enhancing financial access for Micro, Small, and Medium Enterprises (MSMEs). Services such as digital payments, online lending, and automated financial recording are considered capable of improving efficiency, financial literacy, and the competitiveness of MSMEs. This study aims to analyze the effect of fintech usage on the performance of MSMEs in the Food and Beverage sector in North Jakarta. A quantitative approach was employed using simple linear regression analysis on primary data collected from 37 MSME actors. The results indicate that fintech usage has a positive relationship with MSME performance, with a regression coefficient of 0.0911. However, the effect is not statistically significant, either partially or simultaneously, with a p-value of 0.086. The R² value of 0.0297 suggests that fintech explains only 2.97% of the variation in MSME performance, while the remainder is influenced by other factors. The study concludes that fintech has the potential to support MSMEs, but it needs to be strengthened by financial literacy, marketing strategies, product quality, and managerial capabilities to achieve a more optimal impact.